2011
DOI: 10.1175/2011jcli4075.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Cold Winter Temperatures in Europe under the Influence of North Atlantic Atmospheric Blocking

Abstract: North Atlantic atmospheric blocking conditions explain part of the winter climate variability in Europe, being associated with anomalous cold winter temperatures. In this study, the generalized extreme value (GEV) distribution is fitted to monthly minima of European winter 6-hourly minimum temperatures from the ECHAM5/MPI-OM global climate model simulations and the ECMWF reanalysis product known as ERA-40, with an indicator for atmospheric blocking conditions being used as covariate. It is demonstrated that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
192
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(201 citation statements)
references
References 48 publications
9
192
0
Order By: Relevance
“…The blocking impact on CSs is found to be strongest in winter, consistent with the literature (e.g., Buehler et al, 2011; Sillmann et al, 2011). Blocking anywhere in the Euro‐Atlantic region increases the CS frequency in all of Europe in winter and mostly also in spring and fall, mainly driven by cold advection (see section 4.1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The blocking impact on CSs is found to be strongest in winter, consistent with the literature (e.g., Buehler et al, 2011; Sillmann et al, 2011). Blocking anywhere in the Euro‐Atlantic region increases the CS frequency in all of Europe in winter and mostly also in spring and fall, mainly driven by cold advection (see section 4.1).…”
Section: Discussionsupporting
confidence: 90%
“…The role of the extraordinary atmospheric conditions caused by the blocking in the development and maintenance of the Russian HW was discussed by many studies in the aftermath (e.g., Galarneau et al, 2012; Lupo et al, 2012; Miralles et al, 2014; Schneidereit et al, 2012). Conversely, blocking has also been connected to winter CSs (e.g., Buehler et al, 2011; Sillmann et al., 2011), mainly through the advection of cold air (e.g., Bieli et al, 2015; Sousa et al, 2018). Recently, also the blocking impacts during the transition seasons such as spring have come into focus (e.g., Brunner et al, 2017; Cassou & Cattiaux, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are some assumptions in this method that are worth mentioning. The use of short blocks is relatively common in climate studies (Zhang et al 2010;Sillmann et al 2011;Whan et al 2015a) but assumes that a month of observations is long enough for the distribution of maxima to be well approximated by the GEV. Fitting the GEV via maximum likelihood further assumes that there is no relationship between maxima in different months (apart from the possible influence of the covariates, as discussed below).…”
Section: Methodsmentioning
confidence: 99%
“…If such circulations are sufficiently strong and persistent they can divert weather systems from their normal path inducing significant climate anomalies, including extreme climatic events (e.g. Silmann et al 2011). Recent studies identified significant decadal to multidecadal variations in the blocking frequency over Greenland (McLeod and Mote 2016;Hanna et al 2016) and the whole North Atlantic region (e.g.…”
Section: Introductionmentioning
confidence: 99%